Cumulative cyclophosphamide dose and serum anti-Mullerian hormone levels in adolescent cancer survivors in Indonesia - Mulatsih, Sri; Ayuandari, Sarrah; Rahmawati, Naafi Rizqi; Oktasari, Rizki; Dewanto, Agung (Indonesian Pediatric Society, 2023)
Background As both the prevalence and survival rates of cancer in children and adolescents has risen, longer-term effects of cancer treatment must be investigated. High-risk gonadotoxic chemotherapeutic agents such as cyclophosphamide may affect the ovarian reserve and impact female adolescent fertility. Anti-Mullerian hormone is a reliable marker to assess ovarian reserve. Objective To assess for a possible correlation between the cumulative dose of cyclophosphamide and serum anti-Mullerian hormone (AMH) levels among adolescent cancer patients. Methods This cross-sectional study included 12-18-year-old adolescent female cancer patients who had experienced menarche and received cyclophosphamide therapy. We recorded the patients’ full history, including menstrual history, computed the cumulative dose of cyclophosphamide received, and measured serum AMH levels. The correlation test was performed to evaluate for a possible correlation between the cumulative dose of cyclophosphamide and ovarian reserve as represented by AMH levels. Results Out of 12 female adolescent cancer patients, three complained of disturbances in their menstrual cycles. Low levels of AMH (<1.5 ng/mL) were noted in five patients. Median cumulative cyclophosphamide dose was 1,000 mg/m2 (range 1,000 to 5,250 mg/m2). Cumulative cyclophosphamide dose was negatively correlated with serum AMH levels, but this correlation was not statistically significant (r=-0.316, P=0.318). Conclusion This study has not been able to show a correlation between cumulative cyclophosphamide dose and serum AMH level. Regular evaluation of fertility and involvement of fertility team is recommended in adolescents receiving high-risk gonadotoxic chemotherapeutic agents.